180k views
3 votes
What is the simplified form of the following expression?

What is the simplified form of the following expression?-example-1

2 Answers

5 votes

Answer:

A

Explanation:

User Pravchuk
by
6.2k points
1 vote

Answer:


√(3)


Explanation:

We will be using 2 properties of radicals in this simplification (outlined below).


  • √(a*b)=√(a)* √(b)

  • √(a)*√(a)=a

Let's simplify this:


2√(27) +√(12) -3√(3)-2√(12)\\ =2√(9*3)+√(4*3) -3√(3)-2√(4*3) \\=2√(9) √(3) +√(4) √(3)-3√(3)-2√(4) √(3) \\=2(3)√(3)+(2)√(3) -3√(3)-2(2)√(3) \\ =6√(3) +2√(3)-3√(3)-4√(3)  \\=√(3)


First answer choice is right.

User Tiago Matos
by
5.4k points